Red cells from the original JAL+ proband are also DAK+ and STEM+ - Hue-Roye, Kim (2011)
BACKGROUND: The low prevalence Rh antigen, JAL, was named after the index case, Mr. J. Allen. Based on reactivity of seven multi-specific sera with his RBCs, it was apparent that they express at least one additional low prevalence antigen. The purpose of this study was to investigate the other low prevalence antigen(s) on J. Allen’s RBCs. METHODS: Blood samples and reagents were from our collections. Hemagglutination and DNA analyses were performed by standard methods. RESULTS: Our DNA analyses confirmed the presence of RHCE*ceS(340T) in J. Allen and revealed the presence of RHCE*ceBI (ce 48C, 712G, 818T, 1132G) and RHD*DOL (509T, 667T). RBCs from J. Allen were agglutinated by anti-JAL, anti-STEM, and anti-DAK. Two of the reactive multi-specific sera tested in the original paper reacted with RBCs from J. Allen, and with RBCs from four other people with RHCE*ceBI, including the original STEM+ index case (P. Stemper) but not with RBCs with the DIIIa, DAK+ phenotype. We conclude that they contain anti-STEM. CONCLUSION: J. Allen’s RBCs express the low prevalence Rh antigens, JAL, V/VS (extremely weakly), STEM, and DAK. The presence of JAL on the variant Rhce, RhceJAL (16Cys, 114Trp, 245Val), STEM on the variant Rhce, RhceBI (16Cys, 238Val, 273Val, 378Val), and DAK on the variant RhD (170Thr, 223Val), encoded by RHD*DOL in trans to RHCE*ceBI is consistent with expression of these antigens. When J. Allen RBCs are used to detect and identify an anti-JAL, it is important to remember that they also express STEM and DAK.